Versatile Supramolecular Organogel with Outstanding Stability toward Aqueous Interfaces - Bonifazi, Evelyn Lucia (2014)
In this communication we report on a novel and versatile low molecular weight organogelator. The methanolic gel exhibits an exceptional water-enhanced stability as evidenced by a 30oC increase in Tg with up to 10 %v/v of water. This atypical property not observed with other solvents makes of this supramolecular gel a highly stable matrix compatible with aqueous interfaces. As a proof of principle we present the sensing performance of a symmetric tricarbocyanine fluorophore bearing a Zn(II)chelator unit. The system retained its remarkable physical integrity for a long period of time opening new possibilities for other organic-aqueous interface applications.